Birth Preparedness and Complication Readiness among Adult Males in Chengalpattu District, Tamil Nadu, India: A Cross-sectional Study - Vaishnavi Nagarajan; Aamina Hussain; VV Anantharaman (Journal of Clinical and Diagnostic Research)
Introduction: The active participation of males is vital for enhancing maternal and child health outcomes. Supporting mothers in timely healthcare decisions ensures better access to services and care. The World Health Organisation (WHO) defines maternal mortality as deaths caused by pregnancy-related complications or their management within 42 days of pregnancy termination, excluding incidental causes. Birth Preparedness and Complication Readiness (BPCR) is intended to reduce the three primary delays that lead to maternal mortality: delays in recognising the need for medical care, reaching a healthcare facility and receiving timely and proper treatment. Aim: To assess males’ levels of BPCR and identify the factors that influence their participation in these critical aspects of maternal health. Materials and Methods: A community-based cross-sectional study was conducted in Chengalpattu district of Tamil Nadu, India. The research work was carried out from December 2024 to February 2025. The sample size was calculated as 412, and at the end of the data collection, through simple random sampling, 420 samples were collected. Eligible participants were males aged 18 years and above. After obtaining ethical clearance, data collection was carried out using a validated questionnaire adapted from the Johns Hopkins Programme for International Education in Gynaecology and Obstetrics (JHPIEGO) questionnaire devised by The Maternal and Neonatal Health Programme, affiliated with Johns Hopkins University. Data were analysed using Statistical Package for the Social Sciences (SPSS) version 26.0. Descriptive statistics, Chi-square tests, and logistic regression (both bivariate and multivariate) were applied to assess associations among variables. A p-value of <0.05 was considered statistically significant. Results: Among the 420 individuals, 193 (45.95%) were in the 30-39 years age group. Most participants (267, 63.57%) were first-time fathers. Commonly recognised danger signs during pregnancy include nausea and vomiting and severe headaches, which were recognised by 341 (81.2%) and 249 (59.3%) participants, respectively. Multivariable analysis revealed that cultural influence on decision-making was a statistically significant predictor of BPCR, influencing male participation in maternal health planning (AOR=0.091, 95% CI: 0.057-0.143, p-value <0.001). Conclusion: The study infers that early and informed male involvement in BPCR significantly enhances maternal health outcomes, emphasising the need for targeted awareness and engagement strategies.